Talak Tiga yang diucapkan Sekaligus : Studi Komparatif Pemikiran Imam Syafi’i dan Ibnu Taimiyah - Sari, Mia Arina; Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
The study is to explain and analyze the relevance of the views of the Imam Syafi’i and IbnuTaimiyyah about the tree spoken talak at once and look for what the differences and similarities of thethird talak were once pronounced by the Imam Syafi’i dan Ibnu Taimiyyah. The study uses normativejuridical research and research libraries by reviewing the laws and regulations, books, and Islamicjurisprudence (fiqh) books related to the title of this research. Research indicates that according thothe Imam Syafi’i, the opinion in his book of al-Umm is the talak three was spoken at once and that thetalak kept falling away while Ibnu Taimiyyah held in his opinion the three indicators and the talak fellinto one, including the heretic talak and the talak that was shot.